Policy Termination Of Alleged Crime Investigation In Polres Semarang - Jeifson Sitorus; Achmad Sulchan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Police as investigators are authorized to terminate the investigation on the grounds as stated in Section 109 subsection (2) Criminal Procedure Code. In practice, there are crime that have been conducted the investigation found sufficient evidence and suspects, but in fact people who feel harmed (victim) had not wanted the case was brought to trial. This study aims to determine the termination of the investigation policy implementation alleged criminal act in Police Semarang, barriers faced by investigators in the implementation of the termination of the investigation alleged criminal act and analyze the implementation of the termination of the investigation policy alleged criminal act that should be implemented Police. The method used is the juridical sociological with descriptive analytical research specifications. The data used are primary data and secondary data and methods of data collection through field studies and literature. Data analysis method used is qualitative analysis. The results showed that the implementation of the policy of the termination of criminal case investigation in Police Semarang conducted through restorative justice as set out in the SE Chief of Police No. SE / 8 / VII / 2018 so it does not conflict with the provisions of the law. The obstacles faced by investigators in the implementation of the termination of criminal case investigation in Police Semarang consists of internal resistance and external obstacles. As for the implementation of the policy termination criminal case investigation should be carried out in accordance with the provisions of the Police should be legislation that exists, procedural, professional, justice and uphold human rights. Reason for ending the termination of the investigation should be based on the existing Article 109 (2) Criminal Procedure Code and restorative justice with the procedures and provisions stipulated in SE Chief of Police No. SE / 8 / VII / 2018 and the Regulation No. 6 of 2019 concerning the Crime Investigation.Keywords: Termination Of Investigation; Alleged Criminal Act.